Adsorptive behavior of thallium using Fe3O4-kaolin composite synthesized by a room temperature ferrite process. (June 2022) - Luo, Peng-Cheng; Tu, Yao-Jen; Chan, Ting-Shan; Zhu, Jian; Duan, Yan-Ping; Sun, Ting-Ting; Zhang, Zhi-Bo
Abstract: Thallium (Tl) contaminants pose serious threats to the ecological environment and human health due to its acute/chronic poisoning on the health of most organisms even at low concentrations. To find a rapid and efficient technology in removing Tl from waters thus becomes a crucial issue. A magnetic Fe3 O4 -kaolin composite (denoted by FKC) with high specific surface area (133.7 m 2 /g) was successfully synthesized via a simple and low-cost technique for Tl(I) removing from various water media. The HRTEM images confirmed the existence of lattice fingers Fe3 O4 and displayed that a large number of Fe3 O4 nanoparticles dispersed on the surface of kaolin sheets. Compared with kaolin or Fe3 O4 alone, FKC enhanced obviously the adsorption rate and capacity of Tl(I) over a wide pH range (4.5–9.0). The maximum adsorption capacity of FKC for Tl(I) was 19, 347 mg/kg (calculated by Langmuir model), which was almost one hundred times and two times higher than those of kaolin and Fe3 O4, respectively. Importantly, FKC was observed to have a great potential in removing Tl(I) from surface water, groundwater, and tap water in more alkaline conditions. By applying the external magnetic field, FKC could be recovered efficiently (99%) and rapidly (20 s). Moreover, Tl L 3 -edge XANES spectra revealed that Tl(I) was adsorbed on the FKC and would not be converted to more toxic Tl(III). The cations (CaCl2, NaCl, and KCl) and the ionic strength with concentrations of 0.001–1.0 mol/L showed a great influence on the adsorption of Tl(I) by FKC, implying that this adsorption was dominated by outer-sphere surface complexation at investigated pH values. The information provided is essential for designing a rapid and effective scavenger for removing Tl in various natural waters. Graphical abstract: Image 1 Highlights: FKC was synthesized by immersion technique and room temperature ferrite process. In alkaline condition, FKC was a great candidate in Tl removal from natural waters. L 3 -edge XANES showed that Tl(I) was adsorbed and would not be converted to Tl(III). The outer-sphere surface complexation was observed in the adsorption of Tl by FKC. FKC was rapidly and efficiently recovered by applying an external magnetic field.